The therapeutic effects of distinct exercise types on metabolic syndrome-induced reproductive system impairment in male rats: Potential contribution of mitochondria-related genes - Karaman, Muhammed Emre; Tektemur, Ahmet (Wiley, 2022)
A sedentary lifestyle and high fructose dietary habits cause diseases, such as metabolic syndrome (MS). The study was aimed to investigate the potential ameliorative effects of different exercise interventions on high fructose-induced MS-mediated reproductive system disruption of male rats. Rats were divided into four groups (n = 6): Control, MS, MS+aerobic exercise (AE) and MS+anaerobic exercise (ANE). MS was induced by using tap water containing 30% fructose for 8 weeks. After the induction of MS, AE/ANE implementations were started for 6 weeks. Testis tissue and serum samples of rats were stored for biochemical and molecular analyses. Serum total antioxidant status level increased in the MS+AE group compared to all groups. Also, serum total oxidant status level, which increased by MS, decreased with AE, but not altered with ANE. Moreover, MS markedly decreased serum luteinizing hormone, but not changed the follicle-stimulating hormone. However, serum hormone levels were similar to the control group in both MS+AE and MS+ANE groups. MS upregulated mitochondria-related genes' mRNA expressions (MFN2, PGC1A, PPARG, PARP2 and TXNL4B). These increases, except for PPARG, were normalized with both exercise types. These results revealed that mitochondria-related genes may have a crucial role in MS-mediated male reproductive impairment and therapeutic effects of exercises.
Keywords: exercise therapy; metabolic syndrome; mitochondria; oxidative stress; reproductive system